Recuperación urbana el parque de las Jirafas comuna 8 Ibagué- Tolima (2023)
A zonal park will be built in the Ciudadela Simón Bolívar neigborhood, which will help to improve the deficit of square meters of public space per inhabitant and will create a connection between the neighborhood and the expansion zone (Via airport)